PENERAPAN WILLIAM FLEXION EXERCISE, NEURODYNAMIC TENSION DAN NEURODYNAMIC SLIDER SEBAGAI UPAYA PENGURANGAN NYERI PUNGGUNG BAWAH DI KECAMATAN MOJOLABAN SUKOHARJO - Dita Mirawati; Agustina Ellen Dyah Ayu Ellen; Intan Febriana Utam; Mellina Puspita Rahmawati; Vina Devi Kurniawati (Universitas 'Aisyiyah Surakarta, 2023)
Low Back Pain (LBP) or associated low back pain with stress/strain of back muscles, tendons, and ligaments that are usually felt after doing excessive activities, such as lifting heavy weights wrong, bending too long, standing/sitting too long with the position wrongly, lower back pain that arises can result in loss and interfere with work productivity. William flexion exercise is a type of exercise with the concept of spinal flexion Consists of seven sets, aims to reduce pain and provide stability on lower trunk. The purpose of this activity is to provide education to the people of Laban Kulon Village which aims to make the community understand how to handle it, how to prevent it, and how to avoid low back pain. The service activities carried out in Laban Kulon Village RT 02 RW 2 Laban, Mojolaban Sukoharjo on Sunday, March 20, 2022 went smoothly. Based on the results of previous observations and interviews, many residents complained of lower back pain due to their lifestyle and daily activities. The majority are farmers and labourers. The risk factors for myogenic low back pain are the habit of lifting weights too often, sitting and lying down for a long time, sleeping in an uncomfortable position, obesity and lack of exercise. bending or body position during static work.